Virus Secret Revealed by Thermodynamics - Durrani, Mehvish K.; Warren, Abbey N. (My University, 2020)
In regard to recent viral outbreaks, transmissibility is of huge public health concern. Although many variables contribute to how transmissible or infectious a virus is, viral stability plays a critical role. In an effort to decipher the stability of viruses based on their structural properties, we gathered data on various kinetic parameters surrounding the stability of viruses with respect to temperature. Specifically, eight viruses with single-stranded RNA genomes and human hosts were chosen. From this data, the van Hoff relationship was used to extrapolate thermodynamic parameters. On the basis of our analysis, we discovered two characteristics of virus stability that have not previously been reported. Results show that enthalpy-entropy compensation holds true for viral stability indicating that there is limited variability in the stability with respect to condition. It is also found that a strong correlation exists between thermodynamic parameters and genome length. We expect that the insight obtained from this research will be directly applicable to new emerging pathogenic viruses.